The Phenomenon of Flypaper Effect on Fiscal Transfer and Regional Expenditure in Regencies/Cities of West Papua Province in 2017–2021 - La Ode Alisyah; Ketysia Imelda Tewernusa; Nita Dwi Jayanti (Sean Institute, 2025)
This study aims to analyze the influence of Regional Original Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH) on Regional Expenditure and identify the phenomenon of flypaper effect in districts/cities in West Papua Province for the 2017–2021 period. The data used is secondary data obtained from the Directorate General of Financial Balance and the Central Statistics Agency. The analysis method employed is panel data regression, with model selection conducted through the Chow test and the Hausman test, which yields the Fixed Effects Model (FEM) as the best model. The results of the study show that PAD, DAU, and DBH do not have a significant effect on Regional Expenditure, while DAK has a considerable impact. These findings indicate a flypaper effect, where local governments are more responsive to fiscal transfers than to Regional Original Revenue. This condition reflects the fiscal dependence of local governments on central funds, so a strategy to increase PAD is needed to strengthen regional financial independence